Artful sentences : syntax as style - Tufte, Virginia (Graphics Press LLC, 2006)
"In Artful Sentences: Syntax as Style, Virginia Tufte shows how standard sentence patterns and forms contribute to meaning and art in more than a thousand wonderful sentences from the twentieth and twenty-first centuries. The book has special interest for aspiring writers, students of literature and language, and anyone who finds joy in reading and writing."--Publisher's description.